Public art as a catalyst for sustainable communities: the Rock Island Corridor and Raytown, Missouri - Kraus, Daniel L. (Kansas State University, 2012)
Anticipating a thirty five percent population increase over the next thirty years, the Mid-America Regional Council (MARC) developed the Creating Sustainable Places: A Regional Plan for Sustainable Development in Greater Kansas City (CSP) as a comprehensive strategy to guide the Greater Kansas City Metropolitan Region (KC Metro) to grow sustainably into the future. The Rock Island Corridor (RIC) is one of six key corridors identified by the Smart Moves Regional Transit Vision Alternatives Analysis to be redeveloped with the first phase extending seventeen miles from Downtown Kansas City, MO to Pleasant Hill, MO. Phase one will include a mixed use trail and commuter rail line with the second phase planning to extend the mixed use trail to Windsor, MO; becoming the primary link between the KC Metro and the 238 mile long Missouri Katy Trail State Park. Reactivating the RIC, having zero gateways and untouched for thirty years, suggests the corridor communities will require a true collaboration to develop the gateways as destinations at the proposed commuter rail stations. Involving an artist(s) with the interdisciplinary professionals during the entire gateway development project will allow public art to be more successfully integrated into the proposal from the onset. Proposing collaborative gateway design process guidelines, with background information on public art and the collaborative process, will guide the corridor communities in creating a destination for the RIC and the individual communities “achieving the shared vision of creating more vibrant, connected and green centers and corridors” (MARC CSP 2011, 1). Raytown, Missouri is used as an example demonstrating the materials which should be discussed during the initial design meeting in the collaborative gateway design process between the Consultant Team and the Design Advisory Council. Thinking of the RIC as an alternative transit amenity, establishing a collaborative design process and a general understanding of its components will allow for a true collaborative process to develop a destination for the community, the RIC, and KC Metro. Including public art in the collaborative design process will encourage more community involvement, potentially fostering a greater sense of ownership in the gateway, and personal investment in the community; engaging the residents to establish the foundation for a sustainable community capable of developing socially and economically over time.
Keywords: Public art; Collaboration; Guidelines; Sustainable redevelopment; Landscape Architecture (0390)